Caries in primary molars of 6-7-year-old Turkish children as risk indicators for future caries development in permanent molars - Asli Topaloglu-Ak; Ece Eden (Elsevier, 2010)
The aim of the present study was to investigate whether caries existence in the primary dentition at the age of 6-7 years can serve as a test to predict subsequent caries in the permanent first molars. Clinical examinations were carried out in suboptimal conditions of a school-based screening, where non-cavitated enamel caries could not be recorded. Materials and methods: Caries were recorded at baseline and 4 years later in 286 Turkish children aged 6-7 years old. Spearman's correlation coefficients between variables of the caries experience of the primary dentition at the age of 6-7 years and caries in the permanent first molars at the age of 10-11 years were calculated. The area under the ROC curve was used as a measure of predictive accuracy. Results: Caries experience of the primary dentition (dmft), primary molars (dmft molars), and primary second molars (dmft 2nd molars) showed a statistically significant correlation with caries (DMFT) 4 years later in the permanent first molars. Among the variables, the caries experience of the primary second molars was the most powerful caries predictor, which resulted in a value of 0.69 under the ROC curve. Conclusion: With the selection criterion "dmft2ndmolars = 0" in this low-caries-incidence pediatric population, it was possible to identify children truly negative for misclassification.